Physical analysis of temperature-dependent effects of amplitude-modulated electromagnetic hyperthermia. (1st January 2019) - Wust, Peter; Ghadjar, Pirus; Nadobny, Jacek; Beck, Marcus; Kaul, David; Winter, Lukas; Zschaeck, Sebastian
Abstract: Purpose: Preclinical studies and clinical observations suggest that amplitude modulation (AM) below 100 kHz may enhance the intratumoral power absorption of radiofrequency hyperthermia at 13.56 MHz; however, it remains unclear whether AM induces temperature-dependent effects. Methods: We established tumor models assuming typical tumor architectures or cell suspensions to analyze the effects of additional power dissipation. The preconditions for demodulation at cell membranes in situ were outlined. The bioheat transfer equation was solved analytically for the selected models and the possibility of circumscribed temperature increases (point heating) with dependency on the specific absorption rate (SAR) peaks was estimated for centimeter down to nanometer scales. Results: Very-low-frequency (VLF) AM radiofrequency can increase the SAR in the extracellular space or necrosis of tumors as compared to radiofrequencies alone. Such modulation-derived SAR peaks can induce higher temperatures (hot spots) in tumors with necrotic areas of millimeter to centimeter size. However, for lesions <1 cm, excessive (unrealistic) SAR > 1000, 10, 000 and 10 14  W/kg for diameters of ∼5 mm, ∼1 mm and ∼10 nm (nanoheating), respectively, would be required to explain the cell kill observed in pre-clinical and clinical data, even with VLF modulation. Conclusion: Our analysis suggests that VLF AM of radiofrequency hyperthermia for a theoretical tumor model cannot induce relevant temperature-dependent effects, as the associated temperature increases caused by the resultant SAR peaks are too small. Further investigation of possible non-temperature-dependent effects is recommended.